Trauma-Informed Care as a Promising Avenue for Supporting the Transition to Adulthood Among Trauma-Exposed Youth: A Scoping Review - Alexandra Matte-Landry; Annabelle Lemire-Harvey; Amélie de Serres-Lafontaine; Vanessa Fournier (Trauma Care)
Background/Objectives: Childhood trauma has a documented impact on development, and may also affect functioning and well-being in transition-age youth (TAY). There is a need to explore approaches, such as trauma-informed care (TIC), to enhance the services provided during the transition to adulthood. The objective of this scoping review was to explore the extent of the literature on the potential of TIC for supporting TAY. Methods: We focused on initiatives grounded in TIC to support TAY between the ages of 14 and 25 who have histories of trauma. The search strategy involved nine databases and the gray literature. The titles, abstracts, and full text were screened in duplicate by reviewers, and then data were extracted. Results: A total of 19 references were included and classified into three categories: (1) importance of TIC to support TAY (k = 5); (2) description of TIC initiatives (k = 6); and (3) evaluation of TIC initiatives supporting TAY (k = 2). Seven references were classified into more than one category. The references documented 10 TIC models or initiatives, half of which were evaluated and showed promising results. Important components of TIC initiatives supporting TAY included staff training and support; collaborative and multidisciplinary work; systemic changes; addressing trauma and its impacts; and a strength-based and youth-focused approach. Conclusions: The review emphasizes the importance of acknowledging and responding to trauma and its impact in TAY and advances the core components of TIC in the context of the TA, including its systemic nature. Although we cannot conclude that TIC is effective in supporting the TA at the moment—given that the literature is still in its early stages—the review shows that it is at least promising. Limitations, as well as future lines of work are discussed.